The hobbit an unexpected journey - Nesbitt, James, 1965-; Stott, Ken, 1955-; Freeman, Martin, 1971-; Serkis, Andy.; Armitage, Richard, 1971-; Turner, Aidan, 1983-; Jackson, Peter, 1961-; Walsh, Fran, 1959-; Cunningham, Carolynne; Boyens, Philippa; McKellen, Ian.; Blanchett, Cate, 1969-; et al. (Burbank, CA : Warner Home Video, 2013)
The first chapter in Peter Jackson's new epic trilogy set in Middle Earth 60 years before J.R.R. Tolkien's Lord of the rings saga. Follow Bilbo Baggins as he's swept into a quest to reclaim the Dwarf Kingdom of Erebor, long ago conquered by the dragon Smaug. Approached by the wizard Gandalf, Bilbo joins a company of thirteen dwarves led by the legendary warrior Thorin Oakenshield. Along the way they face many dangers; Bilbo meets Gollum and takes possession of the 'One ring.' Includes bonus features.
DVD ; widescreen (16x9) presentation ; dual-layer format ; Dolby digital 5.1 surround.
In English, dubbed French or dubbed Spanish, with optional subtitles in English, French or Spanish ; subtitled for the deaf and hard of hearing.
Ian McKellen, Cate Blanchett, Hugo Weaving, James Nesbitt, Ken Stott, Martin Freeman, Andy Serkis, Richard Armitage, Aidan Turner.
Music, Howard Shore ; editor, Jabez Olssen ; director of photography, Andrew Lesnie.
Based on the novel by J.R.R. Tolkien.
DVD release of the 2012 motion picture.
Keywords: Video recording for the hearing impaired; Middle Earth (Imaginary place); Baggins, Bilbo; Hobbits (Fictitious characters); Baggins, Bilbo (Personaje literario).; Hobbits (Personaje literarios).; Fantasy films; Action and adventure films; Feature films; Fiction films; Video recordings for the hearing impaired